Efficient wheat germ agglutinin purification with a chitosan‐based affinity chromatographic matrix - Baieli, María Fernanda (2012)
An efficient affinity chromatographic matrix based on chitosan for wheat germ agglutinin(WGA) purification was developed. The matrices assayed consisted of chitosan minispheres cross-linked with epichlorhydrin 45, 250 or 500 mM. The maximum adsorption capacity of pure WGA ? calculated from the corresponding isotherms ? was between 43.2 and 48.9 mg/g at pH 5.0 and between 16.6 and 27.6 mg/g at pH 8.5. However, the adsorption of agglutinin from wheat germ extract was higher at pH 8.5. In addition, 0.5 g of mini-spheres cross-linked with epichlorhydrin 250mM adsorbed 94.5% of the WGA present in 5mL of the concentrated extract. Acetic acid was able to elute 100% of the adsorbed WGA. The purity of the WGA obtained was greater than 95% and the purification factor was 56.8. The matrix was able to maintain an efficient performance of the purification process for three consecutive cycles. A new method to monitor the purification process by RP-HPLC was developed.